Unité nationale et inégalités régionales d'accès à l'éducation dans le nord du Nigeria : une source de conflits - Marc Antoine Pérouse De Montclos; Camille Noûs (Les éditions de la Maison des sciences de l'Homme, 2022)
This article studies how educational regional variations contributed to feed development disparities and conflicts between Northern and Southern Nigeria since the colonial era. It also analyses the stereotypes resulting from this educational gap, from the Biafra secession war to the Boko Haram jihadist insurgency today.